HUMAN PAPILLOMA VIRUS. NEW OPPORTUNITIES FOR VACCINATION - A. G. Gaivoronskaya; M. V. Fedoseenko; D. A. Novikova; N. E. Tkachenko; T. A. Grechukha; F. Ch. Shakhtakhtinskaya; M. I. Broeva; L. S. Namazova-Baranova ("Paediatrician" Publishers LLC, 2014)
One of the most important problems in the modern world is the papilloma virus infection. As is known, this is the most widely spread sexually-transmitted infection. The human papilloma virus is responsible for the occurrence of such a terrible disease as cervical cancer, which ranks third after breast cancer and cancer of the body in the structure of oncological morbidity organs of the reproductive system and mammary glands in women. The other manifestations of the papilloma virus infection are pointed condyloma genital warts, which occur frequently both in men and in women. The only reliable method of the prevention of the papilloma virus infection is immunization. The authors present new data regarding the use of bivalent vaccine, including a new scheme of immunization for girls from nine to fourteen years old. Foreign investigations showed that the double scheme of introduction of the vaccine in young girls is as effective as a triple scheme of introduction in the category of women over 15 years of age.